Financial Literacy, Religiosity, and MSME Compliance with Sharia Financing: Does Mental Accounting Matter? - Ai Netty Sumidartiny; Sugiyarti Fatma Laela (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Purpose: This study examines the effect of Sharia financial literacy and religiosity on micro, small, and medium enterprises’ (MSMEs) compliance with Sharia financing contracts. In particular, it explores the mediating role of mental accounting in shaping contract adherence. Method: The research employed a quantitative survey design with 100 MSMEs under Perumda Pasar Jaya Jakarta that had participated in Sharia financing for at least one year. Data were collected through structured questionnaires and complemented with qualitative interviews. Structural Equation Modeling– Partial Least Squares (SEM-PLS) was applied to test direct and mediating effects. Findings: The results demonstrate that both Sharia financial literacy and religiosity exert positive and significant effects on MSMEs’ compliance with Sharia financing contracts. However, the mediation analysis reveals that mental accounting does not significantly mediate these relationships, suggesting that while entrepreneurs understand and value Sharia principles, limited financial buffers and urgent liquidity needs prevent them from consistently applying structured accounting practices. Qualitative evidence confirms that many MSMEs mix business and personal funds, rely on fluctuating cash flow, and occasionally delay repayment despite strong religious motivation. Novelty/Value: Unlike in conventional finance, where mental accounting is often framed as a cognitive bias, in Islamic finance, it can function as a constructive form of self-control. By separating accounts for obligatory payments, including zakah and debt repayment, MSMEs with relatively high religiosity treat financial discipline as part of their religious duty. At the same time, Islamic financing practices grounded in ukhuwah and maslahah provide flexibility when liquidity constraints occur, making mental accounting a unique and contextually embedded mechanism for SMEs.